Internal Reasons and the Problem of Climate Change. Issue 160 (1st September 2019) - Hall, David
Abstract : Climate action is conventionally framed in terms of overcoming epistemic and practical disagreement. An alternative view is to treat people's understandings of climate change as fundamentally pluralistic and to conceive of climate action accordingly. This paper explores this latter perspective through a framework of philosophical psychology, in particular Bernard Williams's distinction between internal and external reasons. This illuminates why the IPCC's framework of 'Reasons for Concern' has an inefficacious relationship to people's concerns and, hence, why additional reason giving is required. Accordingly, this paper recommends a model of truthful persuasion, which acknowledges the plurality of people's motivations and sincerely strives to connect the facts of climate change to people's subjective motivational sets.